Leg Spasticity and Ambulation in Multiple Sclerosis. (4th June 2014) - Balantrapu, Swathi; Sosnoff, Jacob J.; Pula, John H.; Sandroff, Brian M.; Motl, Robert W.
Abstract : Background . Spasticity of the legs is common in multiple sclerosis (MS), but there has been limited research examining its association with ambulatory outcomes. Objective . This study examined spasticity of the legs and its association with multiple measures of ambulation in persons with MS. Methods . The sample included 84 patients with MS. Spasticity of the legs was measured using a 5-point rating scale ranging between 0 (normal) and 4 (contracted). Patients completed the 6-minute walk (6 MW), timed 25 foot walk (T25FW), and timed up-and-go (TUG), and O2 cost of walking was measured during the 6 MW. The patients undertook two walking trials on a GAITRite (CIR systems, Inc.) for measuring spatial and temporal parameters of gait. The patients completed the Multiple Sclerosis Walking Scale-12 (MSWS-12) and wore an accelerometer over a seven-day period. Results . 52% (n = 44 ) of the sample presented with spasticity of the legs. Those with leg spasticity had significantly worse ambulation as measured by 6 MW (P = 0.0001, d = - 0.86 ), T25FW (P = 0.003, d = 0.72 ), TUG (P = 0.001, d = 0.84 ), MSWS-12 (P = 0.0001, d = 1.09 ), O2 cost of walking (P = 0.001, d = 0.75 ), average steps/day (P < 0.05, d = - 0.45 ), and walking velocity (P < 0.05, d = - 0.53 ) and cadence (P < 0.05, d = - 0.46 ). Conclusion . Leg spasticity was associated with impairments in ambulation, including alterations in spatiotemporal parameters and free-living walking.